Subclinical Changes in Left Heart Structure and Function at Preschool Age in Very Low Birth Weight Preterm Infants - Chang, Hung-Yang; Chang, Jui-Hsing; Peng, Chun-Chih; Hsu, Chyong-Hsin; Ko, Mary Hsin-Ju; Hung, Chung-Lieh; Chen, Ming-Ren (Frontiers in Cardiovascular Medicine, 2022)
Background: Survivors of preterm birth are at risk of long-term cardiovascular consequences. The objective of this prospective observational study was to assess left heart function at preschool age in preterm children with very low birth weight (VLBW). Methods: We recruited children aged 5–6 years from preterm infants and full-term children. All subjects underwent conventional echocardiography and speckle-tracking echocardiography. The results were compared between the preterm and term groups. Results: Eighty-seven VLBW preterm children and 29 term controls were included in the study. After adjusting for body surface area, the preterm group compared to the full-term group had significantly smaller left ventricular (LV) end-diastolic and end-systolic internal dimensions (31.2 vs 33.5 mm, p = 0.048; and 20.0 vs 21.6 mm, respectively; p = 0.024), lower LV end-diastolic and end-systolic volumes (38.8 vs 46.3 mL, p = 0.024; and 12.8 vs 15.6 mL, respectively; p = 0.008). Left atrial (LA) maximal and minimal volume were also significantly smaller in the preterm group (15.4 vs 18.9 mL, p = 0.017; and 6.2 vs 7.5 mL, respectively; p = 0.018). LV global longitudinal strain (-21.4% vs -23.2%, p < 0.0001) and systolic strain rate (-1.30 vs -1.37 /s, p = 0.001) were significantly lower in the preterm group than in the term control group. LA longitudinal strain was decreased (43.9% vs 52.8%, p < 0.0001) and left atrial stiffness index (0.17 vs 0.14, p < 0.0001) was increased in preterm infants. However, all the measurements in both groups were within normal range. Conclusions: Subclinical changes of left heart structure and function were found in VLBW infants at preschool age. Additional long-term follow-ups of the cardiovascular outcomes are needed in this vulnerable population.